Identifying the impact of social networks on mental and emotional health seeking behaviours amongst women who are refugees from Syria living in Canada. Issue 5 (4th May 2022) - Mahajan, Shreya; Meyer, Samantha B.; Neiterman, Elena
ABSTRACT: Between 2015 and 2017, over 24, 000 Syrian women came to Canada as refugees. Refugees are two to three times more likely than native Canadians to suffer from depression and other mental health challenges. A qualitative approach was taken to understand roles of social networks in shaping the mental and emotional health resource-seeking behaviours of twelve Syrian women who are refugees. Semi-structured telephone interviews were conducted in both English and Arabic. Interviews were audio-recorded, transcribed, and thematically coded using NVivo 12. Findings reveal that (1) families play large roles in teaching and providing information about Canada's health system, including mental health services; (2) Social networks influence assumptions about mental and physical health services; (3) women feel more welcomed into social networks in Canada than in countries of first asylum; and (4) social networks act as alternatives to seeking formal mental and emotional health care. Through first-hand stories and experiences of Syrian women's transitions into Canada, this study identifies the ways in which social networks may help or hinder engagement with mental and emotional health services.